In silico Prediction of Skin Sensitization: Quo vadis? - Ta, Giang Huong; Weng, Ching-Feng; Leong, Max K. (Frontiers in Pharmacology, 2021)
Skin direct contact with chemical or physical substances is predisposed to allergic contact dermatitis (ACD), producing various allergic reactions, namely rash, blister, or itchy, in the contacted skin area. ACD can be triggered by various extremely complicated adverse outcome pathways (AOPs) remains to be causal for biosafety warrant. As such, it is not uncommon to observe that those commercial products such as ointments or cosmetics can meet the topically safe tests in animal and non-animal models including allergy. Europe, nevertheless, has banned animal tests for the safety evaluations of cosmetic ingredients since 2013, followed by other countries. A variety of non-animal in vitro tests such as direct peptide reactivity assay (DPRA), KeratinoSens™, human cell line activation test (h-CLAT), U-SENSTM, and SENS-IS based on different mechanisms have been developed to identify the suspicious sensitizers consequently. A broad spectrum of in silico models, alternatively, to predict skin sensitization have emerged based on various animal and non-animal data using assorted modeling schemes. In this article, we extensively summarize a number of skin sensitization predictive models that can be used in the biopharmaceutics and cosmeceuticals industries as well as their future perspectives, and the underlined challenges are also discussed.